Effect of soil type, organic matter content, bulk density and saturation on clubroot severity and biofungicide efficacy. (8th March 2016) - Gossen, B. D.; Kasinathan, H.; Deora, A.; Peng, G.; McDonald, M. R.
Abstract : Growth room experiments were conducted to assess the interaction of soil type, biofungicides, soil compaction and pathotype/host on infection and symptom development caused by Plasmodiophora brassicae, the cause of clubroot on Brassica spp. In two initial experiments, four soil types (peat soil, mineral soil, non‐calcareous sand, soil‐less mix), two biofungicides ( Bacillus subtilis, Clonostachys rosea ), and two pathotypes (3 and 6, Williams' differential set) were assessed. Differences in clubroot severity associated with soil type were unexpectedly small and variable. Prestop ( C. rosea ) was often more effective than Serenade ( B. subtilis ) at reducing clubroot levels on peat and mineral soils, but less effective than Serenade on sand. Inoculation with pathotype 3 often resulted in a slightly higher mean severity than pathotype 6. The interaction of soil type × biofungicide was similar on both canola ( B. napus ) and Shanghai pak choy ( B. rapa subsp. chinensis ), whether the soil was kept saturated or allowed to drain after inoculation. The impact of soil type on biofungicide efficacy might explain, in part, why biofungicides are more effective in one location than another. The observation that clubroot severity in soil‐less mix was affected by compaction led to an investigation of soil bulk density. Severity was higher in soil‐less mix that was more compacted than in the initial experiments, and was lower in peat and mineral soils when soil bulk density was reduced by adding soil‐less mix. In this study, soil bulk density had a larger impact on clubroot than soil type, organic matter or pathotype.